Future directions for Indian irrigation: research and policy issues - Meinzen-Dick, Ruth S.; Svendsen, Mark (International Food Policy Research Institute, 1990)
This volume evolved from a workshop held at Ootacamund, Tamil Nadu, in April 1988. Special thanks are due to Mr. A. Mohanakrish-nan, who gave the inaugural address, and to Dr. V. Rajagopalan for the concluding remarks. We are very grateful to Dr. P. Kandaswamy, Dr. A. Kandaswamy, and others of Tamil Nadu Agricultural University for arranging the many logistical details for the workshop. We also wish to acknowledge the contributions of the workshop participants, especially the session chairs and discussants, whose comments and insights made the workshop provocative and useful.